Determinants of receiving immediate breast reconstruction: An analysis of patient characteristics at a tertiary care center in the US. (September 2020) - Siotos, Charalampos; Lagiou, Pagona; Cheah, Michael A.; Bello, Ricardo J.; Orfanos, Phillipos; Payne, Rachael M.; Broderick, Kristen P.; Aliu, Oluseyi; Habibi, Mehran; Cooney, Carisa M.; Naska, Androniki; Rosson, Gedge D.
Abstract: Background: Breast reconstruction is an option for women undergoing mastectomy for breast cancer. Previous studies have reported underutilization of reconstructive surgery. This study aims to examine the role demographic, clinical and socio-economic factors may have on patients' decisions to undergo breast reconstruction. Methods: We analyzed data from our institutional database. Using multivariable and multinomial logistic regression, we compared breast cancer patients who had undergone mastectomy-only to those who had immediate breast reconstruction (overall and by type of reconstruction). Results: We analyzed data on 1459 women who underwent mastectomy during the period 2003–2015. Of these, 475 (32.6%) underwent mastectomy-only and 984 (67.4%) also underwent immediate breast reconstruction. After adjusting for potential confounders, older age (OR = 0.18, 95%CI:0.08–0.40), Asian race (OR = 0.29, 95%CI:0.19–0.45), bilateral mastectomy (OR = 0.71, 95%CI:0.56–0.90), and higher stage of disease (OR = 0.44, 95%CI:0.26–0.74) were independent risk factors for not receiving immediate breast reconstruction. Furthermore, patients with Medicare or Medicaid insurance were less likely than patients with private insurance to receive an autologous reconstruction. There was no evidence for changes over time in the way socio-demographic and clinical factors were related to receiving immediate breast reconstruction after mastectomy. Conclusions: Clinical characteristics, sociodemographic factors like age, race and insurance coverage affect the decision for reconstructive surgery following mastectomy. Highlights: We compared breast cancer patients who had undergone mastectomy with or without immediate breast reconstruction. Older age, Asian race, bilateral mastectomy and higher disease stage were independent factors of no reconstruction. Clinical characteristics, sociodemographic factors affect the decision for reconstructive surgery following mastectomy. Abstract : We compared breast cancer patients who had undergone mastectomy only to those who had immediate post-mastectomy breast reconstruction (overall and by type of reconstruction). Older age, Asian race, bilateral mastectomy and higher stage of disease were independent risk factors for not receiving immediate breast reconstruction. Clinical characteristics, sociodemographic factors like age, race and insurance coverage affect the decision for reconstructive surgery following mastectomy for breast cancer.